The factors affecting the inherited retinal disease project in South Africa - Including insights from Genetic Counsellors - Benefeld, Gameda (Department of Pathology, 2023)
The Inherited Retinal Disease (IRD) Biorepository based in the Division of Human Genetics at the University of Cape Town, has conducted research into the molecular basis of IRD since 1990. Historically, and as part of this programme, patients with IRD are recruited and research into the genetic cause of the patient's disease is initiated, with the ultimate objective of identifying the genetic basis of the disease. An important aspect of the project was to feedback results, especially if it had clinical relevance. The aim of the present research project is to identify factors affecting the result delivery process, with a focus on the non-delivery of results. Method A mixed methodology was used to explore the possible factors which affected non-delivery of results. Quantitative data was collected from the IRD biorepository, and the demographics and other characteristics of patients were explored to gain insight into whether any of these features/characteristics had an impact on result delivery. In addition, a qualitative approach was taken to gain insight into the opinions and experiences of genetic counsellors regarding the delivery of results. The data from this combined mixed methods project provided a reasonably comprehensive view of the result delivery process. Results In the quantitative aspect of the project, analysis of the database reveals that the IRD project had recruited 3413 individuals from 1553 families in the study period analysed (1985-2019). Of these, disease-causing mutations have been identified in 1171 individuals (inferring that they were eligible to receive this information as a ‘result'). Of these individuals, there was evidence that 416 had received their results. Deductively, 755 individuals from 191 families had not received their results. Upon closer inspection of the dataset (including the electronic database and physical subject files/records), there was evidence that an additional 76 subjects had received their results, 46 were deceased and 5 entries were duplicated. This reduced those eligible for results to 628 individuals (referred as the primary cohort). This primary cohort of interest could be divided into 131 subjects where there was a categoric statement on the database indicating that the result was not yet delivered, referred to as a high confidence cohort, and 497 subjects where there was no definitive indication on the database that results were given or not, but for whom one presumed result were not delivered. This group is referred to as the low confidence cohort. In this study, an analysis of the primary cohort (n=628), high confidence cohort (n=131) and low confidence cohort (n=497) was carried out. This was done to ascertain whether iii Abstract any trends and characteristics might emerge from the primary cohort which were a logical extrapolation of the respective cohorts. It was found that patients from large families, mostly recruited during the earlier part of the research drive of 1995 to 2004, were more likely not to have received results. Minors were of particular importance in the database as they represented 20.4% (n=128) of the primary cohort and their results ought to have been expedited. More effort was also made to deliver results to affected individuals as the high confidence cohort had more interaction with affected individuals than unaffected, but other characteristics like sex and age did not affect result delivery. From the qualitative data, it was found that the current process of notifying patients/subjects (directly that a result was available), as opposed to through health professionals, had an impact on the result delivery. This is perceived to be the case since the result delivery hinged on personal initiative and the perceived value of the result by the patient. Genetic counsellors also thought that lower socioeconomic background may have contributed to a reduced delivery of results. Conclusion Result delivery in the IRD project was found to be affected by a number of factors, some of which researchers have control over and some that are beyond their control. The qualitative data corroborated some of the findings from the quantitative results. The results from the genetic counsellors' opinions provided additional insights which may play a role in non-delivery of results, some of which are patient related factors. The study therefore provided insights and proposed strategies that can be used to improve the result delivery process.